The short-term aging effects of Polyvinyl Chloride (PVC) and Nano Silica (NS) as modifiers on asphalt binders - Nguyen Hoang Phong (Journal of Forestry Science and Technology, 2024)
Many studies have shown that for a pavement paved with an asphalt-aggregate mixture, to achieve its design life, the asphalt mustn’t age too hard during storage, during the production process, or while on the road. The short-term aging effects of Polyvinyl Chloride (PVC) and Nano silica (NS) as modifiers on asphalt binders were investigated. The physical properties, penetration, softening points, viscosity measurements, dynamic shear rheometer (DSR), and multiple stress creep recovery (MSCR), under the aging conditions of unmodified and modified asphalt were determined for various PVC and NS contents. To simulate the aging in a short term in the laboratory, the rolling thin film oven test was conducted. Obtained results indicated that adding 5% PVC and 1% NS had a significant positive effect on the aging resistance of asphalt binder through increasing 59.49% penetration aging ratio (PAR) values. It was also observed that adding PVC and NS reinforced the aging resistance of the asphalt binder. Nevertheless, adding PVC and NS reduced softening point increment (SPI), viscosity aging index (VAI), as well as rutting factor aging index (AIR). The asphalt binder modified with PVC/NS demonstrated better performance compared to the asphalt binders only modified with PVC or NS. The results of this study demontrate the feasibility of applying the PVC/NS combination treatment to asphalt in practical applications.